Kinerja Guru dan Kompetensi Supervisi Kepala Sekolah di MTsN 2 Pamulang - Kadir Kadir; Mi'raj Mi'raj (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2010)
The research aims to determine whether there is the correlation between the principal’s supervision competence with the teacher’s performances. the research had been held in September to November 2009 at State Islamic Junior High School 2 Pamulang. the research method which has been used is survey by quantitative approach. the technique for finding samples is purposive sampling. the research instruments which have been used are questionnaire instruments by using a likert scale. the result found in the research that there is the correlation between the principal’s supervision competence with the teacher’s performances.